Control systems engineering - Nise, Norman S. (John Wiley & Sons, 2019)
Highly regarded for its accessibility and focus on practical applications, Control Systems Engineering offers students a comprehensive introduction to the design and analysis of feedback systems that support modern technology. Going beyond theory and abstract mathematics to translate key concepts into physical control systems design, this text presents real-world case studies, challenging chapter questions, and detailed explanations with an emphasis on computer aided design. Abundant illustrations facilitate comprehension, with over 800 photos, diagrams, graphs, and tables designed to help students visualize complex concepts. Multiple experiment formats demonstrate essential principles through hypothetical scenarios, simulations, and interactive virtual models, while Cyber Exploration Laboratory Experiments allow students to interface with actual hardware through National Instruments' myDAQ for real-world systems testing. This emphasis on practical applications has made it the most widely adopted text for core courses in mechanical, electrical, aerospace, biomedical, and chemical engineering. Now in its eighth edition, this top-selling text continues to offer in-depth exploration of up-to-date engineering practices.